Health Awareness Among Diabetes Patients in AL Hassa Region Towards The Risk Factors Associated With Diabetes Management: A Field Study in Medical Sociology - Aloudah, Nahedh Salem (Journal of Humanities & Social Sciences, 2020)
The study aimed to explore the degree of health awareness among Diabetes patients in AL Hassa region towards the risk factors associated with diabetes management related to: (personal and health habits, nutrition, treatment and medication, psychosocial and social aspects). To achieve this goals, a descriptive analytical approach was followed, the questionnaire was used as a tool for data collection, and the study applied to a sample of (220) male and female patients with diabetes mellitus over 15 years in the community of AL Hassa. The results showed that the degree of health awareness among Diabetes patients in AL Hassa region towards the risk factors associated with diabetes management was came with a mean of (3.35), a standard deviation (0.923), and with a (medium) degree of health awareness, where the field of (awareness of risk factors related to the psychosocial and social aspects) came first, followed by the field of (awareness of risk factors related to the personal and health habits), followed by the field of (awareness of risk factors related to the nutrition), followed in the last rank by the field of (awareness of risk factors related to the treatment and medication), with means of (3.14, 3.17, 3.43, 3.69), respectively. Also there were a statistically significant differences found at the significance level of (0.05) in the degree of health awareness among Diabetes patients in AL Hassa region towards the risk factors associated with diabetes management attributed to the variable of (gender), in both total degree and first field, and in favor of males, while there were no Statistically significant differences found attributed to the variables of: (age, and educational level), in the total score, and all four fields. The study made some recommendations, the most important of which are: Holding educational seminars in hospitals and health centers to spread health awareness among diabetics about the risk factors related to the disease management, especially the risk factors related to the treatment, medicine and nutrition.
Keywords: health awareness; diabetes; Al-Ahsa region; risk factors; medical sociology